FAK Forms a Complex with MEF2 to Couple Biomechanical Signaling to Transcription in Cardiomyocytes - Cardoso, Alisson Campos; Pereira, Ana Helena Macedo; Ambrosio, Andre Luis Berteli; Consonni, Silvio Roberto; Rocha de Oliveira, Renata; Bajgelman, Marcio Chain; Dias, Sandra Martha Gomes; Franchini, Kleber Gomes (Structure (London), 2016)
Focal adhesion kinase (FAK) has emerged as a mediator of mechanotransduction in cardiomyocytes, regulating gene expression during hypertrophic remodeling. However, how FAK signaling is relayed onward to the nucleus is unclear. Here, we show that FAK interacts with and regulates myocyte enhancer factor 2 (MEF2), a master cardiac transcriptional regulator. In cardiomyocytes exposed to biomechanical stimulation, FAK accumulates in the nucleus, binds to and upregulates the transcriptional activity of MEF2 through an interaction with the FAK focal adhesion targeting (FAT) domain. In the crystal structure (2.9 Å resolution), FAT binds to a stably folded groove in the MEF2 dimer, known to interact with regulatory cofactors. FAK cooperates with MEF2 to enhance the expression of Jun in cardiomyocytes, an important component of hypertrophic response to mechanical stress. These findings underscore a connection between the mechanotransduction involving FAK and transcriptional regulation by MEF2, with potential relevance to the pathogenesis of cardiac disease. [Display omitted] •FAK accumulates into the nucleus of cardiomyocytes in response to mechanical stress•FAK physically interacts with the MEF2 transcription factor through its FAT domain•We report the crystal structures of the FAK FAT domain with the MEF2 dimer•FAK cooperates with MEF2 to control load-induced expression of Jun in cardiomyocytes Cardoso et al. report the crystal structure of the FAK FAT domain in complex with transcription factor MEF2, and present biochemical and cell-based data that FAK upregulates MEF2 transcriptional activity in cardiomyocytes to regulate the expression of the stress responsive gene Jun in response to biomechanical stimulation.